Mechanism of UTP-modulated attenuation at the pyrE gene of Escherichia coli: an example of operon polarity control through the coupling of translation to transcription. - Bonekamp, F (1984)
The pyrE gene of Escherichia coli is part of an operon where it is preceded by an unknown gene (orfE) that ends 8 bp before the start of the symmetry of the UTP-modulated pyrE attenuator. On a plasmid we have inserted this attenuator region in a synthetic cloning site early in lacZ. The resulting structure contains the lac promoter-operator, the first few codons of lacZ, 42 bp of DNA from the orfE end, the pyrE attenuator, and an in-frame fusion pyrE-lacZ+. The synthetic cloning sites have been used to vary the length and reading frame of the translation that begins at the lacZ start and proceeds towards the attenuator. The effects of these variations on pyrE attenuation were determined by monitoring the synthesis of beta-galactosidase from the pyrE-lacZ hybrid gene in cells grown with either low or high pools of UTP. Thus, a very low level of pyrE expression was observed, regardless of UTP pool size, when the translation from the lacZ start ended 31 or 62 nucleotide residues upstream to the pyrE attenuator symmetry, but a proper UTP controlled attenuation could be established if this translation ended only 8 bp before the symmetry region of the attenuator (as the native orfE gene) or 10 bp after this structure. However, a single 'leader peptide' read from only frequently used codons gave a high level of pyrE expression both at high and low UTP pools. These observations indicate that the coupling between transcription and translation determines the degree of mRNA chain terminations at the pyrE attenuator.(ABSTRACT TRUNCATED AT 250 WORDS)